2021
DOI: 10.1001/jamanetworkopen.2021.18830
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported vs Directly Observed Face Mask Use in Kenya

Abstract: Author Contributions: Drs Jakubowski and Egger had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…After state‐wide mask mandates, self‐reported mask wearing did not increase significantly in the US, indicating a disconnect between rules, messaging and actions, and that socio‐behavioural research is needed to reinforce mask wearing (Clapham and Cook, 2021 ). A discrepancy between self‐reported and observed mask wearing was also observed in developing countries such as Bangladesh and Kenya (Abaluck et al ., 2021 ; Jakubowski et al ., 2021 ). Mask wearing became even more difficult to encourage when masks were associated with the expression of political opinions (Mello et al ., 2020 ) and led to refusal of masks by populist movements in several countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After state‐wide mask mandates, self‐reported mask wearing did not increase significantly in the US, indicating a disconnect between rules, messaging and actions, and that socio‐behavioural research is needed to reinforce mask wearing (Clapham and Cook, 2021 ). A discrepancy between self‐reported and observed mask wearing was also observed in developing countries such as Bangladesh and Kenya (Abaluck et al ., 2021 ; Jakubowski et al ., 2021 ). Mask wearing became even more difficult to encourage when masks were associated with the expression of political opinions (Mello et al ., 2020 ) and led to refusal of masks by populist movements in several countries.…”
Section: Discussionmentioning
confidence: 99%
“…The observed small effects sometimes reflect a discrepancy between self‐reported and observed mask use. For example, a study assessing mask use in Kenya by phone survey versus direct observation revealed a vast gap between the two assessments (Jakubowski et al ., 2021 ). While only 12% of people admitted in phone interviews to not wearing a mask in public, 90% of people did not wear a mask when observed.…”
Section: The Benefits Of Wearing Face Masks – Interpretationmentioning
confidence: 99%
“…In Bangladesh, proper mask use remained very low, at around 10-20%, even after the government formally mandated mask use and threatened to fine those who did not comply (Abaluck and Mobarak 2020). An August 2020 phone survey in rural Kenya finds that while 88% of respondents claim to wear masks in public, direct observation in market centers revealed that only 10% actually did so (Jakubowski et al 2021).…”
Section: Mask-wearingmentioning
confidence: 99%
“…Our main outcome measures are direct observations on a) whether a mask is visible and b) whether a mask is being worn properly (covering mouth and nose), as self-reports may overstate mask wearing [3]. Enumerators observed public spaces within villages from a safe distance and recorded the mask use, type and features of mask wearing by passer-by’s.…”
Section: Methodsmentioning
confidence: 99%
“…Although some recommendations are conflicting, evidence suggests that face masks may significantly reduce the spread of SARS-CoV-2 and numerous governments, including Kenya, have issued mask mandates for certain scenarios. However, questions remain on how to effectively promote mask adoption: Despite masks being mandatory, recent evidence shows less than 20% wear them at markets in Western Kenya [3].…”
Section: Introductionmentioning
confidence: 99%